Interventions life in war and peace /c - Annan, Kofi Atta, (1938- ...).; Mousavizadeh, Nader (New York : Penguin Books, 2013)
With eloquence and immediacy, Annan writes about the highs and lows of his years at the United Nations: from shuttle-diplomacy during crises such as Kosovo, Lebanon and Israel-Palestine to the wrenching battles over the Iraq War to the creation of the landmark Responsibility to Protect doctrine.
Prologue: Peacekeeper, Peacemaker -- Independence: African Beginnings -- Promises to Keep: Somalia, Rwanda, Bosnia, and the Trials of Peacekeeping in a World of Civil War -- Sovereignty and Human Rights: Kosovo, East Timor, Darfur, and the Responsibility to Protect -- A Peoples' United Nations: Reforming Global Governance and Restoring the Rule of Law -- The Fate of the Continent: Africa's Wars, Africa's Peace -- Redefining Human Security: The Global Fight Against Poverty and the Millennium Development Goals -- The World's Fault Line: Peacemaking in the Middle East -- The Wars of 9/11: Terror, Afghanistan, Iraq, and the United Nations at the Brink -- Epilogue: Dreams of a Realist.
Includes index.
Keywords: Annan, Kofi A; Since 1989; World politics -- 1989-; Statesmen -- Ghana -- Biography